GnRHa trigger and luteal coasting: a new approach for the ovarian hyperstimulation syndrome high-risk patient?. Issue 1 (January 2018) - Lawrenz, Barbara; Humaidan, Peter; Kol, Shahar; Fatemi, Human M.
Abstract: Final oocyte maturation using gonadotrophin-releasing hormone agonist (GnRHa) is increasingly common as it almost eliminates the risk of developing ovarian hyperstimulation syndrome (OHSS) in high-responder patients. The first studies using this approach showed a poor reproductive outcome when only vaginal progesterone was used as luteal phase support, due to the luteolysis that will develop as a result of LH withdrawal. Timely luteal administration of human chorionic gonadotrophin (HCG) will counterbalance the low LH concentrations and therefore maintain progesterone production from the corpora lutea, however, some patients with a high number of follicles will develop OHSS using this approach. The concept of 'luteal coasting' transfers the experience from follicular phase coasting for OHSS prevention to the early luteal phase for patients having fresh transfers. Daily monitoring of progesterone concentrations is required and a rescue HCG bolus can be administered, once progesterone concentrations drop below 30 nmol/l. This approach reduces the risk of OHSS development in high-responder patients undergoing fresh embryo transfer, without negatively impacting the reproductive outcome.